Pengembangan Potensi Pangan Lokal sebagai Kuliner Khas di Desa Wae Bobok Kabupaten Manggarai Barat - Elisabet Oktaviani Hanggu; Gregorius Antariksa Berybe; Maria Beatriks Rahinart Wellalangi; Novita Masi Dari Tani; Rafael Modestus Ziku; Fransiskus Xaverius Daniel Lumenta (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Wae Bobok, Tanjung Boleng Village, Boleng District, West Manggarai Regency, East Nusa Tenggara (NTT) Province, has several ideal local food potentials to be developed into local specialties. This area has quite good agricultural potential in the form of rice, sweet potatoes, and various other food products. The strategic location of Wae Bobok village makes it a "rest area" for land-crossers in the southern area of West Manggarai. Currently there are several stall managers who take advantage of this opportunity by selling food and beverage products to earn income. Food and beverage products sold are actually still dominated by non-local products obtained from shops or products outside the region. This certainly indicates that the typical regional products of Manggarai have not been able to become the distinctive color of regional culinary delights, even though the local food potential of the regions is quite diverse. Overal the activities that have been carried out by the team of lecturers are to increase knowledge for shop managers in innovating food and beverage products that are processed from local food. Some of the menus taught in this PkM activity are candlenut cake products, candlenut oil products, candlenut satay seasoning, and rice cake. After carrying out PKM activities in Wae Bobok Village, the team of lecturers concluded that the village's natural potential had not been optimally utilized by stall managers to produce food and beverage products. This is very unfortunate considering the strategic location of the village which is a stopover to unwind. The managers are quite enthusiastic in participating in all the activities carried out by the team of lecturers and students of the Hospitality Management DIV and hope that activities like this will be carried out regularly by the campus.